PERAN KEPALA SEKOLAH DALAM MEMBENTUK BUDAYA RELIGIUS PESERTA DIDIK SMA NEGERI 1 SUGIHAN - Yuni Rohimawati, (UNISAN JURNAL, 2024)
The research conducted by the researcher aims to explore and describe in depth the leadership role of the school principal at the Madiun City Scholar Vocational School in the formation of students' religious culture. This research adopted a qualitative descriptive approach and used purposive sampling techniques to select research subjects. The research results reveal that there are six important roles carried out by school principals in efforts to shape students' religious culture, namely: Carrying out leadership functions effectively to ensure that the school's vision and mission, especially regarding the formation of religious culture, can be achieved. Providing teaching, encouragement and direction not only to students but also to teachers and staff, to create an educational environment that is conducive to the formation of a religious culture. Plan and organize activities that support the development of religious culture, ensuring that these activities can be carried out well. Responsible for the preparation, financing and documentation of all school programs and activities related to fostering religious culture. Providing motivation to teachers, staff and students, as well as managing the physical environment and work atmosphere so as to support the creation of a strong religious culture. Observe, supervise and control the implementation of religious culture development activities, to ensure that these activities run in accordance with the plans and objectives that have been set. From this research it can be concluded that the head of Madiun Scholar Vocational School plays a very crucial multifunctional role in shaping students' religious culture, starting from planning, implementing, to evaluating cultural development activities. Success in establishing a religious culture in this school cannot be separated from strong leadership, clear vision, and high commitment from the school principal as well as support from all school stakeholders.